2010
DOI: 10.1038/nature08859
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in alkali-metal-doped picene

Abstract: Efforts to identify and develop new superconducting materials continue apace, motivated by both fundamental science and the prospects for application. For example, several new superconducting material systems have been developed in the recent past, including calcium-intercalated graphite compounds, boron-doped diamond and-most prominently-iron arsenides such as LaO(1-x)F(x)FeAs (ref. 3). In the case of organic superconductors, however, no new material system with a high superconducting transition temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
535
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 485 publications
(570 citation statements)
references
References 20 publications
26
535
5
4
Order By: Relevance
“…In this context both many-body effects and electron-phonon interactions would be important [9,[14][15][16][37][38][39][40]. Finally, let us remind one that after the seminal work by Mitsuhashi et al [1] showing the existence of superconducting phases for potassium-intercalated picene, additional experimental evidence points to a metallic behavior of K 3 picene. See, for example, the observation of orbital hybridization between picene (C 2p) and potassium (K 4s) near the Fermi energy obtained by Yamane and Kosugi [41] using soft x-ray spectroscopies or the zero resistivity measurement by Teranishi et al [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context both many-body effects and electron-phonon interactions would be important [9,[14][15][16][37][38][39][40]. Finally, let us remind one that after the seminal work by Mitsuhashi et al [1] showing the existence of superconducting phases for potassium-intercalated picene, additional experimental evidence points to a metallic behavior of K 3 picene. See, for example, the observation of orbital hybridization between picene (C 2p) and potassium (K 4s) near the Fermi energy obtained by Yamane and Kosugi [41] using soft x-ray spectroscopies or the zero resistivity measurement by Teranishi et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…The pioneering work of Mitsuhashi et al [1] showed superconductivity of potassium-intercalated picene at 7 or 18 K, depending on sample processing. Later, other PAH crystals formed by coronene [2], phenanthrene [3], and dibenzopentacene [4] have also shown superconducting properties according to the temperature behavior of magnetic susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)] has attracted much attention because the solid picene was found to be the first aromatic superconductor upon potassium-doping with a T c (18 K) that is very high as an organic super- conductor [5,6], and also because high hole mobilities (∼5 cm 2 /Vs) were found even in thin film transistors [7,8]. Moreover, picene has higher chemical stability than its isomer, pentacene, as indicated by a larger optical gap [3.11 eV; Fig.…”
mentioning
confidence: 99%
“…1(b)] were grown by physical vapor de-position in a purified argon stream as described elsewhere [5]. The SCs were bound on Cu plate substrates with silver paste (DOTITE, D-550; FUJIKURAKASEI Co.) in air [see Fig.…”
mentioning
confidence: 99%
“…The discovery of high-T c cuprate is a great success of chemical doping in developing a new superconductor, and many other superconductors, such as fullerenes, ZrNCl and picene, have also been discovered. [1][2][3][4] However, the charge carrier density obtained by chemical doping is limited by the chemical solubility of impurity atoms and the solubility limit of many materials is conventionally very low. Therefore, to make high-density carrier doping to be above the limit, such as in high-pressure chemical reactions, laser doping and thin film fabrication, exploration of a new method are necessary.…”
Section: Introductionmentioning
confidence: 99%